Marine Anti-inflammatory and Antioxidant Agents 2.0 (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue “Marine Anti-Inflammatory and Antioxidants Agents 2.0” collects in vitro and/or in vivo experimental investigations highlighting the role of marine-derived bioactive compounds as modulators of inflammation and/or oxidative stress, papers describing the mechanisms of action and molecular interactions of compounds isolated from marine organisms, and comprehensive review articles summarizing knowledge on marine anti-inflammatory and/or antioxidant agents in support of human health.